1996
DOI: 10.3758/bf03197276
|View full text |Cite
|
Sign up to set email alerts
|

Associative retrieval processes in free recall

Abstract: I present a new method for analyzing associative processes in free recall. Whileprevious research has emphasized the prominence of semantic organization, the present method illustrates the importance of association by contiguity. This is done by examining conditional response probabilities in the output sequence. For a given item recalled, I examine the probability and latency that it follows an item from a nearby or distant input position. These conditional probabilities and latencies, plotted as a function o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

56
849
6
5

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 555 publications
(916 citation statements)
references
References 21 publications
56
849
6
5
Order By: Relevance
“…The change in report order is not a modality effect; as we have suggested, it is a strategic shift that reflects subjects' reflection on performance for end-of-list items (although there may be other reasons as well). Figure 9 corroborates the change in report order using a different measure, the conditional response probability (CRP) curve, a measure of the probability of recalling item a immediately followed by item b, conditioned on the recall of b (see Kahana, 1996). The CRP is plotted on the ordinate, with the distance between presented items on the abscissa.…”
Section: Murdock (1962) In His Classic Book Models Of Human Memorysupporting
confidence: 62%
See 1 more Smart Citation
“…The change in report order is not a modality effect; as we have suggested, it is a strategic shift that reflects subjects' reflection on performance for end-of-list items (although there may be other reasons as well). Figure 9 corroborates the change in report order using a different measure, the conditional response probability (CRP) curve, a measure of the probability of recalling item a immediately followed by item b, conditioned on the recall of b (see Kahana, 1996). The CRP is plotted on the ordinate, with the distance between presented items on the abscissa.…”
Section: Murdock (1962) In His Classic Book Models Of Human Memorysupporting
confidence: 62%
“…Early authorities suggested that the change in report documented by the hook does not occur with lists presented visually (e.g., Beaman & Morton, 2000;Kahana, 1996), but they either confounded modality with amount of practice or administered too little practice to allow the hook to develop. In a large experiment, Roberts (1972) compared both visual and auditory presentation (across both list length and rate of presentation), and his data exhibit the hook in both modalities.…”
Section: Murdock (1962) In His Classic Book Models Of Human Memorymentioning
confidence: 99%
“…Two components describe episodic association-TCM describes asymmetric associations between stimuli in episodic recall (Howard & Kahana, 1999;Kahana, 1996;Kahana & Caplan, 2002) Because each state of context in a list of non-repeated items is as similar to its predecessor as it is to the states that follow, t A i provides a symmetric retrieval cue that favors nearby list items in both the forward and backward directions (see Eq. 8).…”
Section: The Context T a Imentioning
confidence: 99%
“…Both of these properties have been observed in immediate (Howard & Kahana, 1999;Kahana, 1996;Ward et al, 2003), delayed (Howard & Kahana, 1999; and continuous-distractor free recall (Howard & Kahana, 1999), as well as serial recall (Kahana & Caplan, 2002;Raskin & Cook, 1937).…”
mentioning
confidence: 94%
See 1 more Smart Citation